Efeito da sedação com xilazina e butorfanol sobre a avaliação de claudicação nos membros pélvicos de equinos - Beck Júnior, Antônio Alcemar (2018)
Perineural and intrasynovial anesthetic blocks are important tools used in the diagnosis of hindlimb lameness. On uncooperative horses, chemical restraint is commonly used for safe and correct anesthetic injection. However, many veterinarians are reluctant to use sedatives to facilitate the procedure because they believe that its analgesic and proprioceptive effects might attenuate the lameness intensity. In this way, the purpose of this study was to investigate whether the sedation with xylazine (0.3 mg/kg) alone or in association with butorphanol (0.01 mg/kg) attenuated the induced hindlimb lameness in horses. Twelve adult horses (9 mares and 3 geldings) considering lameness-free after physical examination and objective lameness assessment with inertial sensors were included in the study. Galvanized steel clamps were placed around the hoof wall and tightened to induce reversible lameness. Horses were randomly allocated in a crossover design (xylazine, xylazine with butorphanol and untreated control). The objective lameness evaluations were performed right before sedation and 20, 30 and 40 minutes after sedation. The quality of sedation was assessed on the same occasions, using a physical and behavioral descriptive scale, and also by measurement of the head height above ground (HHAG). All horses showed clinical signs of sedation during the first 20 minutes after drug injection, indicating that these drugs would be useful as chemical restraint for diagnostic analgesia. The evaluation of lameness improvement after sedation was performed using the repeated measures ANOVA test followed by the Bonferroni’s multiple comparison test (p<0.05). There was no difference in pelvic asymmetry between xylazine, xylazine with butorphanol and control groups at the different evaluation times. Sedation with xylazine alone or associated with butorphanol at the recommended doses, may be used as chemical restraint method to perform anesthetic blocks on the hindlimb without decreasing lameness intensity until 40 minutes following administration.